Équité et efficacité des programmes actuels de sécurité du revenu - Allie, Émile; Lefebvre, Pierre (L'Actualité économique)

(untitled) (HEC Montréal, 1980)
AbstractThe primary objective of income security policies is to see that resources go to those in need. Programs resulting from these policies can be evaluated for their equity and efficiency. Explicit recognition of time as a factor determining resources and needs of families modifies the traditional picture we have of an unidimensional poverty threshold. In this analysis, available time becomes thus an important parameter in the decision to supply labor. This framework is used to analyse a simplified guaranteed income program and then, to evaluate the case of an integration of the Social Welfare and Work Income Supplement programs of Quebec. Those programs are also examined for their effects they may have on family structure.